Resveratrol enhances chemosensitivity of doxorubicin in multidrug-resistant human breast cancer cells via increased cellular influx of doxorubicin - Kim, Tae Hyung; Shin, Yu Jin; Won, A. Jin; Lee, Byung Mu; Choi, Wahn Soo; Jung, Jee H.; Chung, Hae Young; Kim, Hyung Sik (Biochimica et biophysica acta, 2014)
Multidrug resistance is a major problem in the treatment of breast cancer, and a number of studies have attempted to find an efficient strategy with which to overcome it. In this study, we investigate the synergistic anticancer effects of resveratrol (RSV) and doxorubicin (Dox) against human breast cancer cell lines. The synergistic effects of RSV on chemosensitivity were examined in Dox-resistant breast cancer (MCF-7/adr) and MDA-MB-231 cells. In vivo experiments were performed using a nude mouse xenograft model to investigate the combined sensitization effect of RSV and Dox. RSV markedly enhanced Dox-induced cytotoxicity in MCF-7/adr and MDA-MB-231 cells. Treatment with a combination of RSV and Dox significantly increased the cellular accumulation of Dox by down-regulating the expression levels of ATP-binding cassette (ABC) transporter genes, MDR1, and MRP1. Further in vivo experiments in the xenograft model revealed that treatment with a combination of RSV and Dox significantly inhibited tumor volume by 60%, relative to the control group. These results suggest that treatment with a combination of RSV and Dox would be a helpful strategy for increasing the efficacy of Dox by promoting an intracellular accumulation of Dox and decreasing multi-drug resistance in human breast cancer cells. •We studied synergistic effect of resveratrol and doxorubicin.•We studied alteration of multi-drug resistance abilities in breast cancer cells.•Resveratrol would be a helpful agent for increasing the efficacy of doxorubicin.•The mechanism relies on increase of doxorubicin accumulation.